Ectoparasite burden of Blue‐footed Booby chicks depends on combined parental ages. (19th June 2018) - Ramos, Alejandra G.; Drummond, Hugh
Abstract : The probability of Blue‐footed Booby Sula nebouxii fledglings becoming reproductive adults is maximal when one parent is old and the other young, and minimal when both are old or young. No mechanism has been identified to explain this pattern, but here we showed that nestlings with different‐aged parents are the least infested with ticks. This result constitutes preliminary confirmation of the hypothesis that the effect of combined parental ages on probability of recruitment is mediated by offspring immunocompetence. The contribution of immunocompetence and parental care to these parental age effects needs to be unravelled.